Comparison of GLIM, SGA, PG-SGA, and PNI in diagnosing malnutrition among hepatobiliary-pancreatic surgery patients - Zhou, Lingmei; Fu, Jianying; Ding, Zhen; Jin, Kemei; Wu, Runjingxing; Ye, Ling Xiao (Frontiers in Nutrition, 2023)
Objective: To compare the diagnostic value of four tools—the Global Leadership Initiative on Malnutrition (GLIM) criteria, the subjective global assessment (SGA), patient-generated subjective global assessment (PG-SGA), and prognostic nutritional index (PNI) in malnutrition among hospitalized patients undergoing hepatobiliary- pancreatic surgery. Meanwhile, to observe the nutritional intervention of these patients. Methods: Present study was a cross-sectional study, including 506 hospitalized patients who underwent hepatobiliary- pancreatic surgery between December 2020 and February 2022 at Ningbo Medical Center Lihuili Hospital, China. The incidence rate of malnutrition was diagnosed using the four tools. The consistency of the four tools was analyzed by Cohen’s kappa statistic. Data, including nutritional characteristics and nutritional interventions, were collected. The nutritional intervention was observed according to the principles of Five Steps Nutritional Treatment. Results: The prevalence was 36.75, 44.58, and 60.24%, as diagnosed by the GLIM, PG-SGA, and PNI, respectively, among 332 tumor patients. Among the 174 non-tumor patients, the prevalence was 9.77, 10.92, and 32.18% as diagnosed by the GLIM, SGA, and PNI. The diagnostic concordance of PG-SGA and GLIM was higher (Kappa = 0.814, < 0.001) than SGA vs. GLIM (Kappa = 0.752, P < 0.001) and PNI vs. GLIM (Kappa = 0.265, P < 0.001). The univariate analysis revealed that older age, lower BMI and tumorous were significantly associated with nutritional risks and malnutrition. Among 170 patients with nutritional risk, most of patients (118/170,69.41%) did not meet the nutritional support standard. Conclusion: The incidence of nutritional risk and malnutrition is high among patients with hepatobiliary and pancreatic diseases, specifically those with tumors. The GLIM showed the lowest prevalence of malnutrition among the four tools. The PG-SGA and GLIM had a relative high level of agreement. There was a low proportion of nutritional support in patients. More prospective and well-designed cohort studies are needed to confirm the relevance of these criteria in clinical practice in the future.